Given an equation s^2 = s.
The numbers which are the solutions for the given equation can be obtained by solving the equation. The solution of the given equation is as follows:
![\begin{gathered} s^2=s \\ \Rightarrow s^2-s=s-s \\ \Rightarrow s^2-s=0 \\ \Rightarrow s(s-1)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/toqrqr3e79scs2mifjq1k7uj4h3owyumao.png)
Using the zero-product rule, we can say that the above equation holds true if s = 0 or s - 1 = 0. That implies, x = 0 and x = 1 are the solution of the given equation.
Thus, the solutions are x = 0 and x = 1.